Digital Hybridisation and Communication of the Design Process. The Case of Animated GIFs (diségno, 2023)
The visual codification of architectural representation in the 1920s, in its overt globalisation, is being enriched by a series of analogue-digital hybridisations that greatly broaden the spectrum of expressive possibilities of the early digital era: the maturation of quantitative tools (from BIM to GIS and all their possible derivations) is accompanied by many new qualitative visual containers that are the offspring of a digitalisation which is capable of giving space again to the ways and traditions of manual drawing, in its most diverse declinations. Among these, this paper intends to investigate the growing role played by animated GIFs, short recursive digital animations, in the communication of architectural design. Animated GIFs have been present since years in the landscape of the digital images shared on the web and have become a true professional tool, concise and powerful, capable of conveying a visual storytelling that is much closer than one would think to the established forms of architectural drawing. This type of animation plays on the possibility of condensing a (design and cognitive) process in a few seconds, leveraging the communicative power of the well-established codes of architectural representation, enhanced by the cyclical-temporal dimension.They are small but sharp representation tools that deserve careful evaluation, starting from their effective figurative essentiality.
Keywords: animated GIF; dynamic representation; axonometry; hybridisation; zoetrope